STRUKTUR PENGUASAAN LAHAN DAN PENDAPATAN RUMAH TANGGA TANI (Studi Kasus di Kabupaten Kapuas dan Barito Selatan, Kalimantan Tengah) - DEWA K.S. SWASTIKA; ADIMESRA DJULIN; RACHMAT RAMLI (SOCA: Jurnal Sosial Ekonomi Pertanian, 2002)
Agricultural sector in Central Kalimantan is expected to be a leading sector, especially toprovide food and export. Therefore, improvement of technology is badly needed. Theestablishment of Assessment Institute for Agricultural Technology (AIAT) is aimed to dopackaging and dissemination of mature and appropriate technology to meet the localstakeholders and beneficiaries needs. The appropriate technology should be based on thecharacteristics of local bio-physical and socio-economic environment. This article is aimed topresent the baseline condition of land holding and income distribution of farmers in tidalswampy area of Kapuas and dry land in South Barito districts of Central Kalimantan. Theresults of the study showed that the average land holding in South Barito is larger than that ofin Kapuas. Land holding is equally distributed among farmers, shown by Gini Index of 0.28and 0.27, respectively, for ownership and operated. In Kapuas, land holding is relativelyunequal, shown by gini index of 0.42 and 0.49, respectively, for ownership and operated. Theannual household income in Kapuas was Rp 6.5 million or Rp 1,3 million/capita/year, withrelatively unequal distribution among households, shown by Gini Index of 0.44. In SouthBarito, it was Rp 6.9 million or Rp 2,1 million/capita/year and has relatively equaldistribution, reflected by Gini Index of 0.36. Most of household income is spent for foodexpenditure accounting for 67-69 percent in both districts. This performance indicating thatthe farmers still unable to improve their life quality, especially to meet their secondary needs.This implicitly shows that farmer’s capability to form capital accumulation for their farmingis still very low. Therefore, the least cost new technology is required.